Biomedical Engineering Literature: Advanced Reading Skills for Research and Practice (International Journal of Scientific Research and Management (IJSRM), 2024)
Medical engineering is a field of study that combines biological and medical sciences with engineering to develop improved healthcare technologies. It is imperative that you possess a deep understanding of both the material and the technical language used in this rapidly advancing field in order to effectively grasp key topics and navigate the rapidly expanding literature. This paper examines the future of the biomedical engineering profession through the lens of advanced reading strategies. It starts with the assertion that biomedical engineering literature presents three challenges: the level of density is technical, the area is interdisciplinary, and the growth of knowledge is exponential. In the view of the above challenges, the paper discusses various advanced reading skills in relation to biomedical engineers. These skills include the ability to critically read scientific texts, both at a fast pace for an overview and in detail for deeper understanding, to identify key ideas and methodologies relevant to the field, and to assess the validity of scientific claims and data representations. The paper also aims at pointing out how separate elements like the use of systematic reviews, of meta-analysis, of data visualization tools that complement reading, help the researcher in the process of managing gathered information from various sources. This paper describes teaching these skills for both academic and professional practice, with examples of how improved reading competencies can enhance research quality and contribute to innovations in medical technologies, tissue engineering, and clinical trials. Furthermore, the paper aims to discuss the future trends due to the increasing incorporation of continuous learning for addressing the challenges posed by novel technologies including artificial intelligence and nanotechnology that define the future of biomedical engineering. biomedical engineering students require the acquisition of higher order reading skills in preparation for information reading: national and international publications in the engineering profession, policy and technology in support of health care delivery systems, product development, and other purposes. The ideas stated and demonstrated in this paper should be practical to both beginning scholars and veteran professionals in the biomedical engineering field as well as useful for seminar and workshop participants in seminars and workshops on biomedical engineering literature.